A questão habitacional e ambiental em Cotia no limiar do século XXI - Miranda, Ivan Marcelino de (2009)
This research has in view to analyze the process of irregular occupation in two districts of the Cotia town: Panorama Garden and Turiguara Park. The hypothesis that guided the investigation was that the most parto f the inhabitants of the occupated areas irregularally had as origin in São Paulo city, and their dislocation for Cotia was on account of an expulsion process motivated for its impoverishment. Such situation brings as consequence a process of suburbanization of the towns around of the São Paulo city, that allied to a failure of public politics directed to the housing provision toward this population, cause risk situations toward the inhabitants and threat to the environment. In the analyzed cases such processes lead to the occupation of areas of permanent preservation, represented for the occupation of fertile valleys and edge of rivers that are tributaries of the sub-basin of Guarapiranga, therefore, of protection to the sources. The investigation counted on collect historical of formation of the Cotia town, its entailing with the history of the city of São Paulo; it dealt with the politics of popular habitation fomented by the State; e reconstituted the processes of occupation from the memory of its inhabitants